Effects of Land Use Changes on Water Quality in a disturbed Tropical Stream in Njoro, Kenya - Mainuril, Zachary Gichuru; Mironga, John M; M. Mwonga, Samuel M (Journal of Agricultural Extension Management, 2018)
This study investigated the effects of land use /land cover changes on water quality in the Njoro stream over a period of 27 years. Land sat MSS and Land sat ETM+ (path 185, row 31) were used in this study. The Land sat ETM+ image (June 1987, May, 2000 and July, 2014) was downloaded from USGS Earth Resources Observation Systems data webs ite. Remote sensing image processing was done using ERDAS Imagine 9.1. Three Land Use/Land Cover (LULC) classes were established as forest, shrub land and settlement. Severe land cover changes were found to have occurred from 1987-2000, where settlement increased by -52%, shrub land reduced by +19%, and forestry reduced by +72%. In 2000— 2014, settlement increased by -121%, shrub land reduced by +45%, and forestry reduced by +64% (where positive denotes decrease and negative denotes increase). Forestry and shrub land were found to be consistently reducing while settlement was increasing. It was found that 21% of the watershed community used bore hole or tap water, 59% used river water, 19% wells and 1% dams. It was also found that 10 years ago the clarity of water in the stream was higher than the present. It was observed that the water has been increasingly becoming muddy over this period. Water quality assessment showed that Egerton Bridge had the highest Biological Oxygen Demand incubated for 5 days (BOD) of 24mg/l followed by Canning factory, Kenyatta bridge and Njoro bridge each with 20mg/l with the least being Mary Joy followed closely by Confluence and Nessuit with 13 and 14mg/l respectively. Nitrate and phosphate were significantly different among the seven sampling sites. Despite the sediment loads from erosion and the impacts of land cover change, the stream water remained suitable for human consumption.